2019
DOI: 10.1097/iop.0000000000001331
|View full text |Cite
|
Sign up to set email alerts
|

The Sutureless Mullerectomy

Abstract: Purpose: Müller’s muscle-conjunctival resection (MMCR) is a well-known approach for ptosis repair. In its standard fashion, it involves resection of Müller’s muscle and conjunctiva, followed by suturing of the conjunctiva and Müller’s muscle to the tarsus with absorbable or nonabsorbable sutures. The authors herein present their experience in performing MMCR without sutures. Methods: The study was conducted as a retrospective review of 19 patients (34 e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
24
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(25 citation statements)
references
References 17 publications
1
24
0
Order By: Relevance
“…MMCR was first described by Putterman and Urist in 1975 [1], and it has increased in its popularity due to its cosmetic improvement, fast recovery, lack of external scar, and simplicity. MMCR may have several surgical designs [2][3][4] and variable resection lengths, and some studies have compared the results of MMCR with or without tarsectomy [5][6][7]. In our previous surgical experience, MMCR alone without tarsectomy did not achieve satisfactory results in our Asian patients.…”
Section: Introductionmentioning
confidence: 68%
“…MMCR was first described by Putterman and Urist in 1975 [1], and it has increased in its popularity due to its cosmetic improvement, fast recovery, lack of external scar, and simplicity. MMCR may have several surgical designs [2][3][4] and variable resection lengths, and some studies have compared the results of MMCR with or without tarsectomy [5][6][7]. In our previous surgical experience, MMCR alone without tarsectomy did not achieve satisfactory results in our Asian patients.…”
Section: Introductionmentioning
confidence: 68%
“…MMCR was rst described by Putterman and Urist in 1975 (1), and it is gaining its popularity due to its cosmetic improvement, fast recovery, lack of external scar, and simplicity. MMCR may have several surgical designs (2)(3)(4) and variable resection lengths, and some studies have compared the results of MMCR with or without tarsectomy (5)(6)(7). In our previous surgical experience, MMCR alone without tarsectomy did not achieve satisfactory results in our Asian patients.…”
Section: Introductionmentioning
confidence: 68%
“…The resection amount depends on the response to phenylephrine testing. Since then, MMCR has come with a lot of modi ed surgical designs (2)(3)(4). Later on, Perry et al de ned a modi ed algorithm which included tarsectomy into his procedure (7).…”
Section: Discussionmentioning
confidence: 99%
“…One alternative is a sutureless technique was reported by Lauring [6] in 1977. In recent years, sutureless technique has become popular again [11]. Additionally, Ediriwickrema et al [12] reported the single suture MMCR modification and Carruth and Meyer [13] reported the simplified MMCR technique.…”
Section: Discussionmentioning
confidence: 99%
“…Different surgical modalities have been reported that reduce the risk of wound closure-related complications [3-6, 11-13]. Kavanagh et al [4] reported that the MMCR ptosis repair using a fibrin sealant for wound closure is effective for postoperative pain and discomfort compared with sutures.…”
Section: Introductionmentioning
confidence: 99%